Spletno raziskovanje v šolski knjižnici - Novak Zabukovec, Vlasta (Šolska knjižnica, 2013)
The paper seeksto present the specifics of web research which is becoming increasingly common. It describes the advantages and drawbacks, so that we can know them and take them into consideration when doing web research in school library. The following web research approaces are presented: email survey, email interview, web survey, content analysisof web documents. The conclusion touches upon ethical issuesin web research.
Keywords: ankete; e-pošta; etična načela; intervjuji; spletno raziskovanje; šolske knjižnice